Short Communication: Resistance of eleven new hybrid maize genotypes to Turcicum leaf blight (Exserohilum turcicum) - BUDI SETYAWAN; IRFAN SULIANSYAH; ASWALDI ANWAR; ETTI SWASTI (Biodiversitas Journal of Biological Diversity, 2016)
Setyawan B, Suliansyah I, Anwar A, Swasti E. 2016. Short Communication: Antidiabetic screening of some Indonesian marine cyanobacteria collection. Biodiversitas 17: 604-608. Turcicum leaf blight (TLB) is a leaf disease caused by the fungus Exserohilum turcicum (Pass.) Leonard and Suggs. In Indonesia, TLB was first discovered in North Sumatra in 1917 (Van Hall 1929), and now is found throughout Indonesia (Semangun 2008). Losses due to yield decrease will be greater when the plant is infected at the time of flowering and grain filling phase. Resistant varieties are the most effective way of controlling TLB. The purpose of this research was to test 11 new hybrid maize genotypes to determine the level of TLB resistance. The research was conducted in 2 season, usingrandomize complete block design, 3 replication and 2 control genotypes. Based on statistical examinations and CIMMYT (1999) scoring system, it could be concluded that 10 prospective genotypes (90.9%) which were SSU3X28871, SSU3X29131, SSU3X30735, SSU3X45172, SSU3X68276, SSUSX02791, SSUSX06145, SSUSX48274, SSUSX68849 and SSUSX76844 were significantly better than both control genotypes at LSD 5% (ï¡=0.05).